Fleet Telematics Real-time management and planning of commercial vehicle operations - Goel, Asvin; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2008)
In the past 30 years, commercial transport traffic has more than doubled in both Europe and North America. Asian commercial transport traffic over this period of time has likely increased even more. Traffic jams are routine and they can happen in any segment of the highway system at any time. Moreover, manufacturing companies increasingly apply just-in-time practices in order to cut down inventory costs. As any mismatch between supply and demand can result into significant disturbances of manufacturing processes, just-in-time practices necessitate punctual, reliable, and flexible transportation. Emerging technologies in real-time communications systems provide the means for commercial vehicle operators to meet the increasingly complex customer expectations in a highly dynamic environment with unreliable traffic conditions. FLEET TELEMATICS: Real-Time Management and Planning of Commercial Vehicle Operations combines wireless telematics systems with dynamic vehicle routing algorithms and vehicle-positioning systems to produce a telematics-enabled information system that can be employed by commercial fleet operators for real-time monitoring, control, and planning. The book presents a Messaging & Fleet Monitoring System that automatically identifies deviations between the planned and the current state of the transportation system and a Dynamic Planning System (DPS) that provides real-time decision support considering the current state of the transportation system. The DPS uses newly developed dynamic vehicle routing algorithms to find high-quality solutions and adjust schedules and routes immediately.
Telematics -- Commercial Vehicle Operations -- Management information systems -- Models for routing a fleet of commercial vehicles -- Dynamic vehicle routing -- Conclusions.
Keywords: Leadership; Operations research; Decision making; Information technology; Business—Data processing; Regional economics; Spatial economics; Business; Management science; Engineering economics; Engineering economy; Business Strategy/Leadership.; Operations Research/Decision Theory; IT in Business; Regional/Spatial Science; Business and Management, general; Engineering Economics, Organization, Logistics, Marketing